In the equation f(x) = -3( (2-3x^2)^-1/2 + 3x^2(2-3x^2)^-3/2) my text book jumps to the simplification f(x) = -6(2-3x^2)^-3/2) Could someone please explain this simplification?
Follow Math Help Forum on Facebook and Google+
Hello Hefotos Originally Posted by Hefotos In the equation f(x) = -3( (2-3x^2)^-1/2 + 3x^2(2-3x^2)^-3/2) my text book jumps to the simplification f(x) = -6(2-3x^2)^-3/2) Could someone please explain this simplification? Note first that: So we can take out as a common factor: Grandad
Very well explained, thankyou
View Tag Cloud